Pemimpin Profesional Madrasah - MUNDIR, ABDILLAH (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2016)
AbtractProfessional leaders madrasah education institutions is a capable of givingdirection, setting objectives to be achieved, providing a solution for any problems,make decisions, site planning and strategy. He was a terrific in implementing theconcept. He actively communicate, coordinate, supervise and conduct theevaluation. The important thing is he motivate teachers and staff tobecomeprofessional teachers and professional staff. He built the morale and spirit oftogetherness in madrasa education institutions, teach, train, and give advice. Allhope it will materialize when a headmaster has the integrity to lead madrasaheducation institution to become an institution of superior qualityAbstrakPemimpin profesional lembaga pendidikan madrasah adalah seorangyang mampu memberikan arah, menetapkan tujuan yang akan dicapai,memberikan solusi terhadap setiap permasalahan, membuat berbagaikeputusan, perecanaan dan strategi. Ia adalah seorang yang hebat dalampengimplementasian konsep. Ia aktif berkomunikasi, berkoordinasi,mensupervisi dan mengadakan evaluasi. Yang terpenting adalah iamemotivasi para guru dan tenaga kependidikan untuk menjadi guru dantenaga kependidikan yang profesional. Ia membangun moral dansemangat kebersamaan dalam lembaga pendidikan madrasah,mengajarkan, melatih, dan memberi petuah. Semua harapan itu akanterwujud bila seorang kepala madrasah memiliki integritas untukmemimpin lembaga pendidikan madrasah menjadi lembaga yang ungguldan berkualitas.